Efficacy of Chinese auriculotherapy for stress in nursing staff: a randomized clinical trial - Leonice Fumiko Sato Kurebayashi; Maria Júlia Paes da Silva (Universidade de São Paulo, 2014)
OBJECTIVE: this randomized single blind clinical study aimed to evaluate the efficacy of auriculotherapy with and without a protocol for reducing stress levels among nursing staff.METHOD: a total of 175 nursing professionals with medium and high scores according to Vasconcelos' Stress Symptoms List were divided into 3 groups: Control (58), Group with protocol (58), Group with no protocol (59). They were assessed at the baseline, after 12 sessions, and at the follow-up (30 days).RESULTS: in the analysis of variance, statistically significant differences between the Control and Intervention groups were found in the two evaluations (p<0.05) with greater size of effect indices (Cohen) for the No protocol group. The Yang Liver 1 and 2, Kidney, Brain Stem and Shen Men were the points most used.CONCLUSION: individualized auriculotherapy, with no protocol, could expand the scope of the technique for stress reduction compared with auriculotherapy with a protocol. NCT: 01420835